Taxonomy, biology and management of South African sciaenid fish of the genus Umbrina - Hutchings, Kenneth (Department of Biological Sciences, 2014)
This research was initiated in 2001 with the overall objective of providing scientific information relevant to the sustainable management of South African Umbrina species. Previously there was confusion over the identity and distribution of Umbrina species in South African waters and very little was known of their life histories, population dynamics and stock status. Morphological comparison of a large number of South African Umbrina (n = 369) with specimens from the type locality (Canary Islands) confirmed the identity of South African U canariensis Valenciennes, 1843, and allowed for an expanded description of the species. However, differences between specimens of U ronchus Valenciennes, 1843 and those of the second South African species, lead to the resurrection of U robinson; Gilchrist and Thompson 1908, as a valid name for this species. Spatial analysis of South African specimens collected with a variety of gear revealed U robinsoni to be a shallow water species found from the surf-zone to 40 m depth that is targeted by recreational shore anglers and spear fishers, whilst U canariensis occurs predominantly from 40-100m depth and is predominately landed as a by-catch in the inshore trawl fishery. Although both species occur throughout the South African eastern seaboard, U canariensis is most common west of the Kei River, where the continental shelf is wider.